Philosophes au théâtre de l’écriture: Socrate et Anaxagore, Aristophane et Platon - Stella, Massimo (Revista Archai, 2016)
Socrates and Anaxagoras: a most famous duo both in Aristophane’s and in Plato’s writings, which history of philosophy reshaped as a cas célèbre of the doxographic tradition. In this article, we intend to carry out a mnemo-historical (and, therefore, political) enquiry into the vexed question of the relationship between Socrates’ and Anaxagoras’ philosophical thoughts as represented in Plato’s Phaedo and in Aristophanes’Clouds.